A cultura jurídica como referência na construção das dimensões pedagógicas do ensino jurídico: a contribuição do saber multicultural como processo transdisciplinar - Ramalho, Antonio Germano (2014)
This research investigates the model of legal education as criticized for language, regarded as inadequate educational graduation process in the training of legal practitioners. The current model shown disconnected in the face of regulatory framework consisting of the national guidelines of law school, whose pillars of new normative order, configure transformations that aim to meet a humanistic training, requiring new training curriculum policy, broadening the perspectives of the teachinglearning process, to allow the student to acquire skills and abilities built through learning lines (epistemological and juridical), prioritizing interdisciplinary discourses, multidisciplinary and transdisciplinarity. As the literature consulted, there are few records discussing the form of construction of this process and therefore limited Diagnostics indicating what kind of legal culture fuels the creation of Pedagogical Projects of Course. This is the dimension of theoretical discussion that is part of the problem of thesis whose central objective is to identify the set of values and principles contained in the regulatory framework of the guidelines of course, composing the line of legal culture which should be used as a theoretical discourse to the elaboration of Pedagogical Projects of Course. That assumption has led us to investigate other issues that comprise the specific objectives of the research, such as whether teachers have access to these PPPs; If there are Legal Science dialogue with other sciences; If the fundamental axis of the course receives due attention while most important content; If it is true that overcomes even the eminently educational model of positivist speech. In the general context research has technical procedures of literature review and field studies using the hypothetical-deductive method of qualitative approach; understand the importance of literature review, really scarce, and the opinions of teachers in relation to problems of thesis. As a theoretical proposition to refresh the model of course, took off from ideological assumptions based on the line of cultural studies in education, whereas the contribution of Morin, Delors, Eagleton, Adorno, and Alexy as international authors and Bittar, Linhares, Freire and Barreto as national authors. In the dialogue field research confirmed the object of our problem of thesis. There are a number of issues involving the model of legal education. Statements from teachers that integrate some of the major institutions of higher learning in the State of Paraiba do believe the prospect of important epistemological refresh process of legal education, as well as the need to launch new looks in favor of qualification and training of faculty, these actions that arrangements common to other allied problems addressed tend to increase in terms of the quality of teaching and learning process of legal education, while it will comply with the dictates of normative order.